A intervenção teatral nos espaços museais e na escola: perspectivas para um ensino humanizado de ciências - Ronaldo Goncalves Pires (2016)
An alternative to a more humanized science teaching is the inclusion of a historical regard about science, so as it may conceive its evolution through the interaction between people and the aspects that influence them. This work tries to contribute for this purpose through the incorporation of theatrical interventions in the museum and scholar spaces trying to relate the scientific work with the sensitive aspects thatsurround human beings actions. We applied Stanley Lloyd Millers figure as the main character of the theatrical interventions due to his participation in the experimental history of theories involving life origin which experimental apparatus is reproduced in the exhibit calledDemasiado Humano in the Espaço do Conhecimento UFMG. This is also one of the places in which the research takes place. In the museum, we took into account peoples participation and their interaction with the actors, remaking the meaning of the visit to the museum and promoting the creation of a new regard about the exhibit. At school, we carried out the research in the Federal Institute of Minas Gerais, in Santa Luzia Campus, with students from integrated technical course with high school and, at this place, we proposed to value the students curiosity and leadership though the proposition of questions which guided the role play script. As a result of the research, we published an article in a magazine designed for teachers who work on elementary school, presenting the experience and aiming to contribute for the pedagogy practice of these teachers. Furthermore, we promoted the continuity of the actions derived from the research through two projects (one of research and other of extension). Both aims to continue and give visibility for the proposal of inclusion of science history in the learning process and the promotion of a new regard on museum spaces. The scripts of the role plays and the strategies of approaching the people in the museum are mentioned in order to contribute for the groups which intend to use the scientist history in the scholar space or promote similar actions in the museum space.